POSSIBLE ENERGY SPECTRUM OF THE TWO DIMENSIONAL SPATIAL KLEIN-GORDON OSCILLATOR EQUATION - Saul Paulus (SCIENCE NATURE, 2021)
In the present article, one had found a complete energy spectrum and eigen-function of the solution of two dimensional (2D) spatial Klein-Gordon oscillator equation which shows that its relativistic degeneracy energy is related to the eigen-function.